Protoplast mutant selection of Glarea Lozoyensis and statistical optimization of medium for pneumocandin B0 yield-up. Issue 11 (1st November 2016) - Qin, Tingting; Song, Ping; Wang, Xiaoting; Ji, Xiaojun; Ren, Lujing; Huang, He
Abstract: A combination of microbial strain improvement and statistical optimization is investigated to maximize pneumocandin B0 production from Glarea lozoyensis ATCC 74030. Atmospheric and room temperature plasma (ARTP) was used to enhance G. lozoyensis ATCC 74030 in pneumocandin B0 yield. Mutant strain G. lozoyensis Q1 exhibited 1.39-fold increase in pneumocandin B0 production to 1134 mg/L when compared with the parent strain (810 mg/L). Further, the optimized medium provided another 1.65-fold in final pneumocandin B0 concentration to 1873 mg/L compared to the original medium. The results of this study indicated the combined application of a classical mutation and medium optimization can improve effectively pneumocandin B0 production from G. lozoyensis and could be a tool to improve other secondary metabolites production by fungal strains. Graphical abstract: : Rapid mutation of protoplast of Glarea lozoyensis by ARTP and further pneumocandin B0 titer improvement with statistical medium optimization.